8 - A Researcher’s Visit to Italy: Human trafficking and the Nigerian-Sicilian Mafias - Mike Omilusi, (African Sociological Review, 2019)
This essay interrogates the complex nexus between organized crime and migrants within host countries. It specifically focuses on the surge of irregular migrants crossing the Central Mediterranean to Italy and the emergence of Nigerian criminal gangs who have cemented an ignoble but enduring cord with the Sicilian notorious mafia. This network, which took on a life of its own, has changed the traditional map of organised crime on the Island, defying both regional and global measures. The essay expresses concern on how Sicily intends to stop being “the refugee camp of Europe” through increased repatriations in the face of the financial, logistical and humanitarian implications of such an undertaking.